Social determinants and distance from certified treatment centers are associated with initiation of esketamine nasal spray among patients with challenging-to-treat major depressive disorder. Issue 7 (17th February 2023) - Liberman, Joshua; Pesa, Jacqueline; Rui, Pinyao; Joshi, Kruti; Harding, Lisa
Abstract : Indicated for treatment-resistant depression or major depression with suicidal ideation, esketamine (ESK) is self-administered under supervision at certified treatment centers. Our study was to determine if social determinants of health and distance were associated with ESK utilization. We conducted a retrospective cohort study among 308 US adults initiating ESK between October 11, 2019 and December 31, 2020 and 1540 propensity-score matched controls with treatment-resistant depression or major depression with suicidal ideation. Adjusting for demographics, prior health care utilization and comorbidities, social determinant variables and distance were regressed separately on each outcome: ESK initiation, failure to complete induction (8 treatments in 45 days), and discontinuation within 6 months. ESK initiation was associated with higher population density (odds ratio [OR]: 2.12), American Indian, Alaska Native, Native Hawaiian, Other Pacific Islander (OR: 3.19), and mental health (OR: 1.55) and primary care providers (OR: 1.55) per capita. Lower likelihood of ESK initiation was associated with living > 7.2 miles from a treatment center (OR: 0.75), living in rural areas (OR: 0.64), and percent non-Hispanic African American (OR: 0.58) and Hispanic (OR: 0.40). Health care providers should tailor patient engagement strategies to mitigate potential barriers to initiating and continuing appropriate treatment. Failing to complete induction was associated with substance use disorder and longer distance to treatment center was associated with discontinuation (hazard ratio: 1.48), as was percent Asian population (hazard ratio: 1.37). Prior psychiatric care and residence in counties with high rates of primary care providers per capita, unemployment, and high school graduation were associated with both higher likelihood of completing induction and lower likelihood of discontinuation.